Outcome of gamma knife radiosurgery in intracranial arterio-venous malformations: A single institution experience - Maneet Gill; Sudhanshu Agarawal; Ajay Sebastian Carvalho; Chinmaya Srivastava; Darpan Gupta; Vijay Gupta; Diva Rovino (Ukrainian Neurosurgical Journal)
Introduction: Gamma Knife radiosurgery (GKRS) provides in general a high dose ionizing radiation to specific target location, which has already been defined by stereotaxy for the treatment. Arteriovenous malformations (AVMs) are one such indication for GKRS they are rare, occurring at an incidence of 15-18 cases per 100,000 adults, with a rupture rate of 2–4%. GKRS is indicated for small (< 3.5 cm), surgically high-risk, deep-seated and complex AVMs. Successful AVM treatment in GKRS eliminates the risk of intracranial haemorrhage, complete nidal obliteration, limiting the development of new deficit from radiation-induced changes. Materials and Methods: This study was conducted in the Department of Neurosurgery, a tertiary care center , New Delhi for the duration of two years (September 2019 to September 2021). A total of 40 patients (N) were studied. Variables included demographic profile, clinical profile, AVM grading, radiation dose and treatment outcomes particularly nidal obliteration and symptom resolution. The factors which affected obliteration of AVM and six-monthly follow-up were analysed. Results: The study showed among all variables that the initial volume of nidus, duration following GKRS were important predictors for AVM obliteration with statistically significant p-values (<0.05). Conclusion: GKRS is effective treatment modality in AVMs, especially those with low nidus volume, low Spetzler-Martin (SM) grade, deep venous drainage, young age and deep-seated lesions. However, in this study, the p-values were not statistically significant (p-value >0.05) for above parameters. Among all, the initial nidus volume, and the duration of post GKRS for the obliteration of AVM had significant p-values (<0.05).